Synthesis and molecular weight characterisation of rubber seed oil-modified alkyd resins - Aigbodion A I; Pillai C K (Journal of Applied Polymer Science, 2001)
Alkyd resins of 40;, 50;and 60;oil length (OL) are prepared with rubber seed oil (RSO), phthalic anhydride (PA) and glycerol (GLY), employing the two-stage alcoholysis method. Changes in the , physical characteristics of the reaction medium are monitored by determination of the acid value and the number-average molecular weight, Mn, of in-process samples withdrawn at different stages of the reaction. The mode of variation of these properties denotes that the preparation of RSO alkyds is complex. Molecular weight averages and the molecular weight distribution (MWD) of the finished alkyds are determined by GPC, cryoscopy and end-group analysis. Molecular weight averages and the MWD vary with differences in the formulation, with sample II exhibiting the narrowest size distribution.
Source Year: 2001
Keywords: Alkyd resins; Molecular weight; Rubber seed; Rubber seed oil